Big numbers about small children: Estimating the economic benefits of addressing undernutrition - Alderman, Harold; Behrman, Jere R.; Puett, Chloe (Oxford University Press, 2017)
Different approaches have been used to estimate the economic benefits of reducing undernutrition and to estimate the costs of investing in such programs on a global scale. While many of these studies are ultimately based on evidence from well-designed efficacy trials, all require a number of assumptions to project the impact of such trials to larger populations and to translate the value of the expected improvement in nutritional status into economic terms. This paper provides a short critique of some approaches to estimating the benefits of investments in child nutrition and then presents an alternative set of estimates based on different core data. These new estimates reinforce the basic conclusions of the existing literature: the economic value of reducing undernutrition in undernourished populations is likely to be substantial.